Three rhythms - Pickford, Joel:::::::::
Three rhythms. In the summer of 1978, Rollin Pickford exhibited watercolors and acrylics, Doug Walla exhibited wood sculpture, and Joel Pickford exhibited black & white photographs in a three-artist show at the Monterey Peninsula Museum of Art (today, Monterey Museum of Art).